EFEKTIVITAS PROGRAM KREDIT POTONG GAJI BPR BANK DAERAH PATI TERHADAP PERANGKAT DESA KABUPATEN PATI - Hilya Khoirin Nida (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
In short, this study aims to assess the salary deduction credit scheme run by BPR Bank Daerah Pati in collaboration with village officials in Pati Regency. In this study, the author's analytical approach is to describe the stages of data collection by observing the behavior of experts and graduates of accounting programs. In addition, interviews were conducted with a number of bank employees, and secondary data analysis was carried out on internal documents of BPR Bank Daerah Pati. The results, in the period from January 2023 to April 2025 there was a significant increase. Village officials said that the automatic, fast, and minimal delay payment mechanism made this financing very efficient and beneficial. Salary funds at the beginning of the budget year are a significant barrier that has an impact on the BI Checking score, as a result of the selected payments, which causes problems in financing. To overcome this, BPR Bank Daerah Pati implemented blocked savings as a temporary measure. The salary deduction credit program appears to have shown ease of access, rapid credit repayment, and better economic stability at the village level as a whole, despite the obstacles. The effectiveness of this program depends on the comprehensive understanding of savers and efficient collaboration between local governments and banks.